A convoluted concussion case. Issue 3 (3rd April 2022) - Huffer, Kelly Watson
Abstract: Background College health pracitioners are often the primary contact for students with concussion. The aim of this case report is to describe concussion management of a convoluted journey to recovery for a student over the course of an acadmic year. Case presentation The case starts with an initial presenting event which is further complicated by repeated head traumas, co-morbid mental health conditions, and inconsistency with follow-up. Interprofessional collaboration and inclusion of the Zurich protocol eventually lead to resolution of symptoms. Conclusion The emphasis on a multidisciplinary approach to the medical and academic progress is described. Identifying information was changed to protect the student.